2022
DOI: 10.1155/2022/5882346
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Molecular Mechanism of Xijiao Dihuang Decoction for the Treatment of SLE Based on Network Pharmacology and Molecular Docking Analysis

Abstract: Objective. To elucidate the main mechanism of Xijiao Dihuang decoction (XJDHT) for the treatment of systemic lupus erythematosus (SLE). Methods. TCMSP, BATMAN-TCM, ETCM, and TCMID databases and literature search were used to screen the potential active compounds of XJDHT, and TCMSP and SwissProt databases were searched to predict the targets of the compounds. The targets of SLE were obtained from Genegards, OMIM, and DisGeNET databases, and Venn online platform was used to obtain the intersection targets of XJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…YHT active ingredients are represented by orange nodes, menopause targets by blue nodes, and YHT itself by green nodes. The number of links connected to other nodes indicates the importance of a node in the network ( 17 ). Topological analysis of degree revealed that the top 10 active ingredients were: quercetin, genistein, kaempferol, apigenin, estradiol, isorhamnetin, formononetin, nobiletin, epicatechin, and maleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…YHT active ingredients are represented by orange nodes, menopause targets by blue nodes, and YHT itself by green nodes. The number of links connected to other nodes indicates the importance of a node in the network ( 17 ). Topological analysis of degree revealed that the top 10 active ingredients were: quercetin, genistein, kaempferol, apigenin, estradiol, isorhamnetin, formononetin, nobiletin, epicatechin, and maleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…and Paeonia suffruticosa Andr., which has the effect of clearing heat and removing toxins, cooling blood and dispersing blood stasis. 17 While main clinical manifestation of psoriasis is blood heat and blood stasis, which coincides with the main therapeutic effect of XJDHT. However, the exact efficacy of XJDHT in the treatment of psoriasis has yet to be reported, and its underlying mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 94%
“…SLE belongs to the category of “butterfly sore,” “horse sore,” and “sun sore” in the traditional Chinese medicine (TCM). [ 6 ] TCM has good therapeutic prospects and achieves good therapeutic outcomes for SLE due to its low side effects and multi-targeting characteristics. [ 7 ] The TCM theory believes that SLE is usually caused by congenital deficiency of endowment, deficiency of kidney yin, imbalance of yin and yang, imbalance of qi and blood, and stagnation of qi and blood stasis.…”
Section: Introductionmentioning
confidence: 99%